Pengaruh Media Video terhadap Peningkatan Pengetahuan dan Keterampilan dalam Pencegahan Diare Siswa SDN 010 Loa Janan - Lioni Oviana Putri Sangga Sari; Emelia Tonapa; Yona Palin T (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Every year, diarrhea kills 50,851 children aged 5-9 years. In the working area of the Trauma Center Health Center Loa Janan Ilir in 2022, the number of diarrhea cases was 344, and it increased in 2023 to 416. This indicates that personal hygiene practices such as handwashing are not yet optimal. One educational effort that can increase students' interest in improving clean and healthy living behavior is to use video-based learning media, by observing the effect of video media on increasing knowledge and skills in preventing diarrhea among students of SDN 010 Loa Janan Ilir. The method used is a quantitative approach with a pre-experimental design (one group pretest-posttest), with a sample consisting of 45 students from classes 4A, 4B, and 4C of SDN 010 Loa Janan Ilir, selected using proportional random sampling. Data was collected through questionnaires and CTPS observations and then analyzed using the Wilcoxon test. The results showed a significant improvement in knowledge and skills (p-value = 0.000) after the intervention was given. Video media proved to be effective as an educational tool in improving personal hygiene behavior among elementary school students as a preventive measure against diarrhea, and audiovisual media can be an appropriate health promotion strategy in school environments.